2021
DOI: 10.1016/j.jbc.2021.101277
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of SF3B1 in the pre-mRNA spliceosome induces a RIG-I-dependent type I IFN response

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…We next performed gene set enrichment analysis (GSEA), which revealed IFN-α-response as the most significantly enriched pathway in KPC-Sf3b1 K700E/+ tumor cells ( Figure 2—figure supplement 1C ). This result is in line with a previous study, which found that aberrant splicing caused by SF3B1 inhibition or oncogenic SF3B1 mutations induces an IFN-α-response through retinoic acid-inducible gene I (RIG-I) mediated recognition of cytosolic aberrant RNA-species ( Chang et al, 2021 ). Interestingly, epithelial-mesenchymal transition (EMT) emerged as the most significantly attenuated gene set in KPC-Sf3b1 K700E/+ cells ( Figure 2A and B , Figure 2—figure supplement 1C ).…”
Section: Resultssupporting
confidence: 93%
“…We next performed gene set enrichment analysis (GSEA), which revealed IFN-α-response as the most significantly enriched pathway in KPC-Sf3b1 K700E/+ tumor cells ( Figure 2—figure supplement 1C ). This result is in line with a previous study, which found that aberrant splicing caused by SF3B1 inhibition or oncogenic SF3B1 mutations induces an IFN-α-response through retinoic acid-inducible gene I (RIG-I) mediated recognition of cytosolic aberrant RNA-species ( Chang et al, 2021 ). Interestingly, epithelial-mesenchymal transition (EMT) emerged as the most significantly attenuated gene set in KPC-Sf3b1 K700E/+ cells ( Figure 2A and B , Figure 2—figure supplement 1C ).…”
Section: Resultssupporting
confidence: 93%
“…2C). This result is in line with a previous study, which found that aberrant splicing caused by SF3B1 inhibition or oncogenic SF3B1 mutations induces an IFN-α-response through retinoic acid-inducible gene I (RIG-I) mediated recognition of cytosolic aberrant RNA-species (Chang et al, 2021). Interestingly, the most significantly depleted gene set in KPC-Sf3b1 K700E/+ cells was epithelial-mesenchymal transition (EMT) (Fig.…”
Section: Resultssupporting
confidence: 93%
“…The commonly shared enrichment between all three‐cell death EVs according to the low stringent analysis (ribosome biogenesis, RNA splicing, RNP complexes, RNA transport and localization, and RNA export from the nucleus) (Figure S3d ) could be a sign of rapid perturbation of spliceosome‐related processes and nuclear RNA export during any RCD type. The concealing effect of EVs may prevent nucleic acid sensing responses and temper associated inflammatory signalling against spliceosomes and associated factors (Chang et al., 2021 ). In that respect the stringent analysis revealed a bias towards the exclusive enrichment of proteins involved in ribosome biogenesis, rRNA metabolic processing, and (m)RNA catabolic processes in the case of apoEVs and necEVs but not ferEVs.…”
Section: Discussionmentioning
confidence: 99%